Analisis Pengaruh Rasio Keuangan terhadap Kebijakan Dividen pada Perusahaan Food and Beverages yang Terdaftar di BEI Periode 2020-2022 - Chasnalita, Rebyka; Respati, Harianto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research focuses on discussing financial factors as measured by financial ratios because they can provide an overview of company performance. The problem that will be answered in this research is to prove whether financial performance as an independent variable is represented by the ratios: Current Ratio (CR), Return on Equity (ROE), Debt Equity Ratio (DER), Net Profit Margin (NPM) and Earning per Share (EPS) simultaneously or partially has an influence on the dividend payment ratio (DPR) in Food and Beverage companies that go public and to prove which ratio is the most dominant. This study uses a quantitative approach 15 companies which are manufacturing companies in the Consumer Non-Cyclical sector, F&B sub-sector on the Indonesia Stock Exchange (BEI) during the 2020 - 2022 period using the census method. Multiple Regression Analysis is used to test all variables, both simultaneously and partially. The analysis results show that simultaneously Current Ratio, Return on Equity, Debt Equity Ratio, Net Profit Margin and Earning per Share have a significant influence on the Dividend Payout Ratio. Based on these correlation results, it can be concluded that CR, ROE, DER, NPM and EPS are able to explain the diversity of DPR amounting to 64.7%. Meanwhile, partially only ROE, DER and NPM have a significant influence on the Dividend Payout Ratio (DPR). And the variable that has a dominant influence on the Dividend Payout Ratio (DPR) is Return on Equity (ROE) with a correlation value of 0.718 (R2 = 0718).